Autophagy Mediates Leptin-Induced Migration and ERK Activation in Breast Cancer Cells - García-Miranda, Alin; Solano-Alcalá, Karen Aylín; Montes-Alvarado, José Benito; Rosas-Cruz, Arely; Reyes-Leyva, Julio; Navarro-Tito, Napoleón; Maycotte, Paola; Castañeda-Saucedo, Eduardo (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is an intracellular recycling process active in eukaryotic cells that involves the formation of an autophagosome which delivers cytoplasmic components to the lysosome for degradation. This process occurs at low rates under basal conditions, but it can be induced by diverse types of stress such as starvation, hypoxia, metabolic disorders or in response to hormones, including leptin. Leptin is considered a pro-tumorigenic protein whose circulating levels have been related to bad prognosis in obese breast cancer patients. It has been recently demonstrated that leptin can induce autophagy in cancer cell lines from different tissues, suggesting that autophagy could modulate the pro-tumorigenic effects associated with leptin. In this study, the role of autophagy in leptin-induced proliferation, migration, apoptosis and ERK phosphorylation in breast cancer cell lines was evaluated. Although leptin differentially induced autophagy in the breast cancer cell lines tested, autophagy inhibition reduced leptin-induced cell proliferation in MCF7 cells and decreased cell migration, ERK activation, and impaired morphological changes in both cell lines. Our data demonstrates an important role for basal autophagy or leptin-induced autophagy in leptin-induced migration and ERK phosphorylation in breast cancer cell lines, suggesting a potential use for the inhibition of autophagy in breast cancer associated with obesity.